2000
DOI: 10.1590/s0100-879x2000001000015
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the ACTH receptor

Abstract: Adrenal glucocorticoid secretion is regulated by adrenocorticotropic hormone (ACTH) acting through a specific cell membrane receptor (ACTH-R). The ACTH-R is a member of the G protein superfamilycoupled receptors and belongs to the subfamily of melanocortin receptors. The ACTH-R is mainly expressed in the adrenocortical cells showing a restricted tissue specificity, although ACTH is recognized by the other four melanocortin receptors. The cloning of the ACTH-R was followed by the study of this gene in human dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The reduction of plasma aldosterone in the RC/FF mice is probably a consequence of the greatly reduced plasma renin and consequent reduction in angiotensin II signaling. However, since certain signaling pathways in the zona glomerulosa involve cAMP, for example, that is activated by ACTH, we cannot exclude that a reduction of Gs␣ expression in the adrenal gland contributes to this effect (8). Previous studies have shown that a reduction of angiotensin II signaling by angiotensin-converting enzyme or angiotensin receptor blockade or genetic deletion of components of the reninangiotensin system causes a consistent upregulation of COX-2 in MD and TAL cells (6,7,14,34,35).…”
Section: Ren1mentioning
confidence: 93%
“…The reduction of plasma aldosterone in the RC/FF mice is probably a consequence of the greatly reduced plasma renin and consequent reduction in angiotensin II signaling. However, since certain signaling pathways in the zona glomerulosa involve cAMP, for example, that is activated by ACTH, we cannot exclude that a reduction of Gs␣ expression in the adrenal gland contributes to this effect (8). Previous studies have shown that a reduction of angiotensin II signaling by angiotensin-converting enzyme or angiotensin receptor blockade or genetic deletion of components of the reninangiotensin system causes a consistent upregulation of COX-2 in MD and TAL cells (6,7,14,34,35).…”
Section: Ren1mentioning
confidence: 93%
“…MC2R is a member of the G protein coupled superfamily receptors and belongs to the melanocortin receptor family [54 ] . MC2R is mainly expressed in the adrenocortical cells, shows a low expression in skin and adipose tissue, while the pituitary and hypothalamus do not express MC2R [18 ] . In the HPA axis, CRH promotes the release of pituitary ACTH, ACTH circulates to the adrenal cortex where it binds to MC2R.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline 180-min production of both ALDO and 18OH-CORT is markedly higher at day 6 than at day 3 of growth on Matrigel; and iii) Matrigel culture favors the maintenance of the expression of either ACTH and Ang-II receptors or voltage-gated Ca 2+ channels in ZG cells. The steroidogenic effects of ACTH and Ang-II are mediated by the MC2 (27,28) and the AT1 receptors (29), while K + depolarizes the cell plasma membrane with the ensuing opening of L-type Ca 2+ channels (30,31). Tissue culture on plastic causes a time-dependent decrease in the secretory response of ZG cells to all their main agonists, while the growth on Matrigel maintains higher the response to ACTH and Ang-II and unchanged that to K + .…”
Section: Discussionmentioning
confidence: 99%